The clinical outcomes and predictive factors for in-hospital mortality in non-neutropenic patients with candidemia. Issue 23 (June 2016) - Wang, Tsai-Yu; Hung, Chia-Yen; Shie, Shian-Sen; Chou, Pai-Chien; Kuo, Chih-Hsi; Chung, Fu-Tsai; Lo, Yu-Lun; Lin, Shu-Min
Abstract : Abstract: Recent epidemiologic studies have showed that candidemia is an important nosocomial infection in hospitalized patients. The majority of candidemia patients were non-neutropenic rather than neutropenic status. The aim of this study was to determine the clinical outcome of non-neutropenic patients with candidemia and to measure the contributing factors for mortality. A total of 163 non-neutropenic patients with candidemia during January 2010 to December 2013 were retrospectively enrolled. The patients' risk factors for mortality, clinical outcomes, treatment regimens, and Candida species were analyzed. The overall mortality was 54.6%. Candida albicans was the most frequent Candida species (n = 83; 50.9% of patients). Under multivariate analyses, hemodialysis (OR, 4.554; 95% CI, 1.464–14.164) and the use of amphotericin B deoxycholate (OR, 8.709; 95% CI, 1.587–47.805) were independent factors associated with mortality. In contrast, abdominal surgery (OR, 0.360; 95% CI, 0.158–0.816) was associated with a better outcome. The overall mortality is still high in non-neutropenic patients with candidemia. Hemodialysis and use of amphotericin B deoxycholate were independent factors associated with mortality, whereas prior abdominal surgery was associated with a better outcome.